Symbiosis among field beans and Rhizobium leguminosarum bv. phaseoli strains sensitive and resistant to antibiotics and fungicides - Pereira, João Carlos; Vidor, Caio; Lovato, Paulo Emílio; Penteado, Alberto de Figueiredo (Pesquisa Agropecuaria Brasileira, 1991)
Two experiments were conducted in greenhouse to evaluate the response of the interaction between the bean cultivars (Phaseolus vulgaris L.) Bat-76, ICA-Pijao, Porrillo Sintetico, and Turrialba-4 to inoculation with R. leguminosarum bv. phaseoli strains. Cultivar Bat-76 exhibited a low N2-fixing ability in a sand-solution experiment expressed as dry shoot weigh and total N, whereas Porrillo Sintetico showed the low-est dry nodule weight in the soil experiment (Passo Fundo - Oxisol) but with no differences in shoot weight and total N as compared to the other cultivars. The symbiotic ability was variable among the strains. Resistance to antibiotics increased infectivity of strains as measured by nodule number but it did not increase the potential for N2 fixation. Moreover, plants inoculated with strains from serogroup SEMIA 4002 accumulated higher dry shoot weight and total N as compared to serogroup SEMIA 487 in the sand experiment. When grown in soil there was a lower nodule weight from plants inoculated with serogroup SEMIA 4002, suggesting that detrimental soil factors affected nodule initiation and development caused by strains from this serogroup.